Molecular mechanisms of Huanglian Jiedu decoction in treating Alzheimer’s disease by regulating microbiome via network pharmacology and molecular docking analysis - Zheng, Renyuan; Shi, Shenggan; Zhang, Qin; Yuan, Shuqin; Guo, Tong; Guo, Jinlin; Jiang, Peidu (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Huanglian Jiedu decoction (HLJDD) is a famous traditional Chinese medicine prescription, which is widely used in the treatment of Alzheimer’s disease (AD). However, the interaction between bioactive substances in HLJDD and AD-related targets has not been well elucidated. Aim: A network pharmacology-based approach combined with molecular docking was performed to determine the bioactives, key targets, and potential pharmacological mechanism of HLJDD against AD, through the regulation of microbial flora. Materials and Methods: Bioactives and potential targets of HLJDD, as well as AD-related targets, were retrieved from Traditional Chinese Medicine Systems Pharmacology Analysis Database (TCMSP). Key bioactive components, potential targets, and signaling pathways were obtained through bioinformatics analysis, including protein-protein interaction (PPI), Gene Ontology (GO), and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis. Subsequently, molecular docking was performed to predict the binding of active compounds with core targets. Results: 102 bioactive ingredients of HLJDD and 97 HLJDD-AD-related targets were screened. Bioinformatics analysis revealed that kaempferol, wogonin, beta-sitosterol, baicalein, acacetin, isocorypalmine, (S)-canadine, (R)-canadine may be potential candidate agents. AKT1, TNF, TP53, VEGFA, FOS, PTGS2, MMP9 and CASP3 could become potential therapeutic targets. 15 important signaling pathways including the cancer pathway, VEGF signaling pathway, and NF-B signaling pathway might play an important role in HLJDD against AD. Moreover, molecular docking analysis suggested that kaempferol, wogonin, beta-sitosterol, baicalein, acacetin, isocorypalmine, (S)-canadine, and (R)-canadine combined well with AKT1, TNF, TP53, VEGFA, FOS, PTGS2, MMP9, CASP3, respectively. Conclusion: Our results comprehensively illustrated the bioactives, potential targets, and possible molecular mechanisms of HLJDD against AD. HLJDD may regulate the microbiota flora homeostasis to treat AD through multiple targets and multiple pathways. It also provided a promising strategy for the use of traditional Chinese medicine in treating human diseases.